Assessing the Effectiveness of Environmental Sustainability Performance Communication in Tourism: Mediation and Moderation Effects - Jishnu Bhattacharyya (Journal of Travel Research, 2024)
This study aims to examine how and when different framings of sustainability performance communication influence travelers’ behavioral intentions. Specifically, it examines (1) the effectiveness of sustainability performance communication framing in shaping traveler’s behavioral intentions, (2) the mediating role of perceived commitment to sustainability, and (3) the moderating effect of the level of sustainability performance communicated. The findings of the four experiments conducted revealed that communicating sustainability performance is more effective than not reporting it in determining travelers’ behavioral intentions. Furthermore, an enhancement framing is more effective when communicating sustainability performance than a reduction framing. We also found that tourism provider’s commitment to sustainability explains the impact of sustainability performance communication framing on behavioral intentions. Furthermore, we found that communicating a moderate level of sustainability performance in enhancement framing and a high level in reduction framing is effective. The study provides implications for theory and practice in developing effective sustainability communication.